Characterization of D-Arabitol as Newly Discovered Carbon Source of Bacillus methanolicus - López, Marina Gil; Irla, Marta; Brito, Luciana F.; Wendisch, Volker F. (Frontiers in Microbiology, 2019)
Bacillus methanolicus is a Gram-positive, thermophilic, methanol-utilizing bacterium. As a facultative methylotroph, B. methanolicus is also known to utilize D-mannitol, D-glucose and, as recently discovered, sugar alcohol D-arabitol. While metabolic pathways for utilization of methanol, mannitol and glucose are known, catabolism of arabitol has not yet been characterized in B. methanolicus. In this work we present the elucidation of this hitherto uncharted pathway. In order to confirm our predictions regarding genes coding for arabitol utilization, we performed differential gene expression analysis of B. methanolicus MGA3 cells grown on arabitol as compared to mannitol via transcriptome sequencing (RNA-seq). We identified a gene cluster comprising eight genes that was up-regulated during growth with arabitol as a sole carbon source. The RNA-seq results were subsequently confirmed via qRT-PCR experiments. The transcriptional organization of the gene cluster identified via RNA-seq was analyzed and it was shown that the arabitol utilization genes are co-transcribed in an operon that spans from BMMGA3_RS07325 to BMMGA3_RS07365. Since gene deletion studies are currently not possible in B. methanolicus, two complementation experiments were performed in an arabitol negative Corynebacterium glutamicum strain using the four genes discovered via RNA-seq analysis as coding for a putative PTS for arabitol uptake (BMMGA3_RS07330, BMMGA3_RS07335 and BMMGA3_RS07340 renamed to atlABC) and a putative arabitol phosphate dehydrogenase (BMMGA3_RS07345 renamed to atlD). C. glutamicum is a natural D-arabitol utilizer that requires arabitol dehydrogenase MtlD for arabitol catabolism. The C. glutamicum mtlD deletion mutant was chosen for complementation experiments. Heterologous expression of atlABCD as well as onlz the arabitol phosphate dehydrogenase gene atlD from B. methanolicus alone restored growth of the C. glutamicum ΔmtlD mutant with arabitol. Furthermore, D-arabitol phosphate dehydrogenase activities could be detected in crude extracts of B. methanolicus and these were higher in arabitol-grown cells than in methanol- or mannitol-grown cells. Thus, B. methanolicus possesses an arabitol inducible operon encoding, amongst others, a putative PTS system and an arabitol phosphate dehydrogenase for uptake and activation of arabitol as growth substrate.